2016
DOI: 10.1515/popore-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial and algal diversity in the vicinity of two different seabird colonies in Spitsbergen

Abstract: Abstract:The aim of the study was to compare cyanobacterial and algal assemblages occurring in ornithocoprophilous habitats formed under the influence of two seabird colonies (mixed colony of piscivorous Uria lomvia and Rissa tridactyla and planktivorous Alle alle) nesting on the southwest side of Hornsund (Spitsbergen). Various influences of the bird colonies (e.g. surface trophy, treading) lead to the formation of ornithogenic habitats with quantitatively and qualitatively diverse cyanobacterial and algal as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This macroscopic alga colonizes nests because it is an extremely nitrophilous taxon, found in nesting areas of birds in the north pole, being common in all habitats rich in organic nitrogen (Broady et al 2012, Richter et al 2014. Unfavorable habitat conditions caused by constant treading by birds change the algal mat to a monostromatic lamellar, cracked form, which was also observed in our study (Pietryka et al 2016). In our study 38,5% of the nests a ring of this alga is found in the first ring together with the rock fragments of the nest (including inactive nests), where feces deposition is higher.…”
Section: Discussionsupporting
confidence: 84%
“…This macroscopic alga colonizes nests because it is an extremely nitrophilous taxon, found in nesting areas of birds in the north pole, being common in all habitats rich in organic nitrogen (Broady et al 2012, Richter et al 2014. Unfavorable habitat conditions caused by constant treading by birds change the algal mat to a monostromatic lamellar, cracked form, which was also observed in our study (Pietryka et al 2016). In our study 38,5% of the nests a ring of this alga is found in the first ring together with the rock fragments of the nest (including inactive nests), where feces deposition is higher.…”
Section: Discussionsupporting
confidence: 84%
“…The growth of microalgae and plants in Arctic regions is limited by factors such as temperature, water availability, and nutrient supply. Therefore, these parameters are usually taken into account in studies focusing on the relationships between algae or plants and habitat conditions (e.g., [26,[70][71][72][73]). Some studies conducted in polar habitats indicated the major influence of basic nutrients in the formation of cyanobacterial and algal assemblages [23,41,46].…”
Section: Discussionmentioning
confidence: 99%
“…Seabird guano is a rich source of nitrogen (NO 3 − , NH 4 + ), potassium (K + ) and phosphate (PO 4 3− ), and affects other physicochemical properties, e.g., soil/water conductivity and reactivity; thus, it is the most important driver of ecological conditions [49][50][51][52]65,72]. Hence, this factor has a strong effect on the structure of plant and phycoflora communities in the Hornsund Fjord area [46,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…(Matuła et al, 2007; Richter et al, 2009). However, the detailed qualitative and quantitative studies conducted in the same locations revealed that cyanobacterial and algal assemblages were also differentiated by the colony type (Pietryka et al, 2016). The ornithogenic communities G1 and G2 were largely devoid of lichens, except for the ornithocoprophilous Physcia spp.…”
Section: Discussionmentioning
confidence: 99%